A Natural Experiment on Job Insecurity and Fertility in France - Andrew E. Clark; Anthony Lepinteur (Institute of Labor Economics (IZA), 2020)
Job insecurity can have wide-ranging consequences outside of the labour market. We here argue that it reduces fertility amongst the employed. The 1999 rise in the French Delalande tax, paid by large private firms when they laid off workers aged over 50, produced an exogenous rise in job insecurity for younger workers in these firms. A difference-in-differences analysis of French ECHP data reveals that this greater job insecurity for these under-50s significantly reduced their probability of having a new child by 3.9 percentage points. Reduced fertility is only found at the intensive margin: job insecurity reduces family size but not the probability of parenthood itself. Our results also suggest negative selection into parenthood, as this fertility effect does not appear for low-income and less-educated workers.
Keywords: I38; J13; J18; 330; employment protection; layoff tax; perceived job security; difference-in-differences; fertility